2004
DOI: 10.1037/h0088890
|View full text |Cite
|
Sign up to set email alerts
|

Child-Centered Kinder Training for Teachers of Pre-School Children Deemed At-Risk.

Abstract: Pronchenko-Jain, B. A. (2012). Child teacher relationship training (CTRT) with children exhibiting disruptive behavior: Effects on teachers' ability to provide emotional and relational support to students and on student-teachers relationship stress (Doctoral dissertation). Retrieved from https:// search.proquest.com/docview/1335545982 Resilience and Learning Project. (2019). Public school forum of North Carolina: Resilience and learning project. Retrieved from https://www.ncforum.org/ north-carolina-resilience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
4
34
1
Order By: Relevance
“…Studies have also indicated that play therapy conducted by parents (filial therapy) is a valid treatment method to address children's problematic behaviors. Adaptations have been made to the filial therapy model to include teachers as therapeutic agents (Brown, 2002;Guerney & Flumen, 1970;Post, McAllister, Sheely, Hess, & Flowers, 2004;Smith & Landreth, 2004;White, Flynt, & Draper, 1997,) in an effort to improve child-teacher relationships. However, one tenet of filial therapy and, additionally, filial therapy training with teachers, is the expectation that after learning and practicing the relationship-building skills with an individual child in a play room purposefully structured to include specific toys and materials , many of those skills will transfer for use with all children in the classroom.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also indicated that play therapy conducted by parents (filial therapy) is a valid treatment method to address children's problematic behaviors. Adaptations have been made to the filial therapy model to include teachers as therapeutic agents (Brown, 2002;Guerney & Flumen, 1970;Post, McAllister, Sheely, Hess, & Flowers, 2004;Smith & Landreth, 2004;White, Flynt, & Draper, 1997,) in an effort to improve child-teacher relationships. However, one tenet of filial therapy and, additionally, filial therapy training with teachers, is the expectation that after learning and practicing the relationship-building skills with an individual child in a play room purposefully structured to include specific toys and materials , many of those skills will transfer for use with all children in the classroom.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…To date, only one research study has investigated whether or not teachers are able to maintain the use of play therapy skills in the classroom over time (Hess, Post, & Flowers, 2005). Additionally, little research has investigated what impact, if any, there is on children's behavior as a result of the teacher's use of play therapy skills in the classroom (Post et al, 2004)…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Play therapy has been successful in improving children's behavioural problems including hyperactivity, inattention, cognitive problems, aggression, and conduct problems (Draper et al, 2001;Packman & Bratton, 2003;Post, McAllister, Sheely, Educational Psychology in Practice 193 Hess, & Flowers, 2004;Ray et al, 2007), whilst improving the child's presentation of anxiety and depression, and improving their adaptive skills, including social skills, adaptability, leadership and study skills (Post et al, 2004). In a school-based play therapy intervention, teachers reported significant reductions in aggressive problem behaviours for those children who received the intervention compared to those in the control group (Ray, Blanco, Sullivan, & Holliman, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In a study where teachers in 2-, 3-, and 4 year-old classrooms were trained in a 10 week filial therapy method, Post, McCallister, Shelly, Hess, and Flowers (2004) found that children who were deemed at risk possessed fewer cognitive, social, and emotional school-readiness skills. After administering the BASC, the Assessment of Child-Centered Play Therapy Skills, and the Measurement of Empathy in AdultϪChild Interaction (MEACI) in a pre-and posttest study, the researchers found that teachers who went through the kinder training sessions showed improved ability to use play therapy skills and demonstrate empathy toward children.…”
Section: Adaptations Of Cprt With Other Populationsmentioning
confidence: 99%